Pengaruh kedisiplinan, perhatian orang tua dan jumlah saudara terhadap prestasi belajar matematika - Eko Budiono (Annals of Mathematical Modeling, 2019)
Penelitian bertujuan untuk mengetahui : (1) pengaruh kedisiplinan siswa terhadap prestasi belajar Matematika, (2)  pengaruh perhatian orang tua terhadap prestasi belajar matematika, (3) pengaruh jumlah saudara terhadap prestasi belajar matematika siswa, (4) pengaruh kedisiplinan, perhatian orang tua dan jumlah saudara terhadap prestasi belajar matematika siswa kelas XII SMK Taman Karya  Kabupaten Purworejo Penelitian ini menggunakan pendekatan kuantitatif. Populasi adalah siswa kelas XII SMK TKM Teknik Tamansiswa di Kabupaten Purworejo berjumlah 360 siswa. Sampel diambil dengan teknik proportional random sampling dan terpilih sampel 158 siswa. Pengumpulan data menggunakan angket, sebelumnya dilakukan uji validitas dan reliabilitas. Analisis data menggunakan analisis deskriptif, pengujian prasyarat analisis. Pengujian hipotesis menggunakan teknik product moment dan regresi linier. Hasil penelitian (1) terdapat pengaruh positif yang signifikan antara variabel kedisiplinan siswa terhadap prestasi belajar matematika pada siswa SMK TKM Teknik Tamansiswa Purworejo. (2) terdapat pengaruh positif yang signifikan antara perhatian orang tua terhadap prestasi belajar matematika pada siswa SMK TKM Teknik Tamansiswa Purworejo. (3) terdapat negatif yang signifikan antara jumlah saudara terhadap prestasi belajar matematika pada siswa SMK TKM Teknik Tamansiswa Purworejo (4) terdapat pengaruh positif yang signifikan antara kedisplinan siswa perhatian orang tua dan jumlah saudara terhadap prestasi belajar matematika pada siswa SMK TKM Teknik Tamansiswa Purworejo. Besarnya todal sumbangan efektif variabel bebas adalah 65,5 % meliputi kedisiplinan siswa 43,7 %, perhatian orang tua 32,3 % dan jumlah saudara -10,5 %. Sumbangan relatif kedisiplinan siswa 66,7 %, perhatian orang tua 49,3 % dan jumlah saudara – 16,0 % sehingga total adalah 100 %. Influence of discipline, parent's attention and number of brothers on mathematics learning achievement AbstractThe study aims to determine: (1) the influence of student discipline on Mathematics learning achievement, (2) the influence of parental attention on mathematics learning achievement, (3) the influence of the number of siblings on student mathematics learning achievement, (4) the influence of discipline, parental attention and the number of siblings towards mathematics learning achievement of students of class XII SMK Taman Karya Purworejo Regency This study used a quantitative approach. The population is students of class XII Tamansiswa Technical TKM Vocational School in Purworejo Regency, amounting to 360 students. Samples were taken by proportional random sampling technique and selected samples of 158 students. Data collection uses questionnaires, previously tested the validity and reliability. Data analysis used descriptive analysis, analysis prerequisite testing. Hypothesis testing uses product moment techniques and linear regression. The results of the study (1) there is a significant positive effect between the students' disciplinary variables on mathematics learning achievement in the Vocational School students of Tamansiswa Purworejo Technical TKM. (2) there is a significant positive effect between parental attention to mathematics learning achievement on SMK students of Tamansiswa Purworejo Technical TKM. (3) there is a significant negative between the number of siblings towards mathematics learning achievement in Tamansiswa Purworejo Vocational School TKM students (4) there is a significant positive influence between students 'discipline of parents' attention and number of siblings on mathematics learning achievement in Tamansiswa Purworejo Vocational School TKM students. The magnitude of the effective contribution of the independent variable is 65.5% including student discipline 43.7%, the attention of parents 32.3% and the number of siblings -10.5%. The relative discipline of students contributed 66.7%, the attention of parents was 49.3% and the number of siblings - 16.0% so the total was 100%.